Pengaruh Partisipasi Masyarakat terhadap Efektivitas Pembangunan Desa Majasari Kecamatan Sliyeg Kabupaten Indramayu - Fandi Ahmad; Ono Taryono (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2021)
The implementation of development should be carried out in harmony between the development programs carried out by the central government, regional governments and village governments.Therefore, you can imagine that if development is not accompanied by community participation, it is impossible to handle it by the government itself and will not be successful evenly and sustainably. The mixed method approach is used as the basis for a research approach in which the researcher tries to fully describe the conditions or situations faced by utilizing the data from field observations and then adding a literacy study whose results are processed again with a linear regression approach to determine the relationship between variables that influence each other. From the results of the data processing of the results of the research, information was obtained that the existence of community participation in the village development process is the realization of a strategy in an effort to observe and investigate the needs and various problems faced by the village community and determine various development programs in order to meet the needs and answer various problems. there is this and with community participation, it is hoped that village development will succeed in achieving its goals and targets.